2018
DOI: 10.1016/j.jconrel.2018.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Potent in vivo lung cancer Wnt signaling inhibition via cyclodextrin-LGK974 inclusion complexes

Abstract: Activation of the Wnt signaling pathway promotes lung cancer progression and contributes to poor patient prognosis. The porcupine inhibitor LGK974, a novel orally bioavailable cancer therapeutic in Phase I clinical trials, induces potent Wnt signaling inhibition and leads to suppressed growth and progression of multiple types of cancers. The clinical use of LGK974, however, is limited in part due to its low solubility and high toxicity in tissues that rely on Wnt signaling for normal homeostasis. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…We believe it is likely that either the accumulation of specific oncogenic events, or prolonged in vitro culture relieved their WNT dependence, confounding the correlation of TNKSi response and APC/WNT alterations. Indeed, one recent study in lung adenocarcinoma demonstrated that WNT/RSPO-dependent 3D organoid cultures become WNT-independent when cultured in 2D (35). Further, Lord and colleagues recently proposed that activating Kras mutations may correlate with resistance to TNKS inhibitors (36).…”
Section: Discussionmentioning
confidence: 99%
“…We believe it is likely that either the accumulation of specific oncogenic events, or prolonged in vitro culture relieved their WNT dependence, confounding the correlation of TNKSi response and APC/WNT alterations. Indeed, one recent study in lung adenocarcinoma demonstrated that WNT/RSPO-dependent 3D organoid cultures become WNT-independent when cultured in 2D (35). Further, Lord and colleagues recently proposed that activating Kras mutations may correlate with resistance to TNKS inhibitors (36).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term treatment with WNT974 can cause intestinal and bone damage in mice (22,23). To enable potent and sustained WNT suppression in tumor cells without effects on surrounding tissues, we used the regulatable shApc model, whereby withdrawal of dox from chow drives rapid APC restoration and potent WNT pathway suppression (10,11).…”
Section: The In Vivo Tumor Microenvironment Is Sufficient To Prime Cementioning
confidence: 99%
“…The earliest uses of supramolecular macrocycles in drug delivery were in the context of excipients which functioned primarily by improving the solubility and formulation stability of a diverse array of hydrophobic drugs and increasing cell permeability for charged species 15-17. In addition, there are examples using inclusion within supramolecular macrocycles as a method to mitigate the toxicity of a drug 18. These uses are typically characterized by equilibrium-governed interactions between a drug guest and a hydrophilic macrocycle host.…”
Section: Introductionmentioning
confidence: 99%